2022
DOI: 10.1002/anie.202207459
|View full text |Cite
|
Sign up to set email alerts
|

Transparent and Colorless Dye‐Sensitized Solar Cells Based on Pyrrolopyrrole Cyanine Sensitizers

Abstract: The development of transparent solar cells extends the applications of photovoltaics by offering the opportunity to substitute the gigantic surface coverage of windows by solar panels to produce electricity. Herein, we report a new family of NIR‐sensitizers based on pyrrolopyrrole cyanine dyes, particularly efficient for the development of fully transparent and colorless dye‐sensitized solar cells since a record efficiency of 2.5 % was achieved with an average visible transmittance (AVT) of 76 % and a color re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…PPCy is known to take the form of π-planar stacking in the aggregated state . Based on its structure, any change in the molecular polarity and shape should lead to a certain degree of change in intermolecular aggregation. ,,, It is rather remarkable that due to the coordination of boron groups, the absorption spectrum of the molecules will be significantly red-shifted and narrowed . Such fascinating properties are very important for the preparation of NBA-OPDs with spectral responses in the NIR region.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PPCy is known to take the form of π-planar stacking in the aggregated state . Based on its structure, any change in the molecular polarity and shape should lead to a certain degree of change in intermolecular aggregation. ,,, It is rather remarkable that due to the coordination of boron groups, the absorption spectrum of the molecules will be significantly red-shifted and narrowed . Such fascinating properties are very important for the preparation of NBA-OPDs with spectral responses in the NIR region.…”
Section: Results and Discussionmentioning
confidence: 99%
“…22,35 Some PPCy dyes exhibit NIR absorption, high fluorescence brightness, large molar extinction coefficient, and excellent photothermal stability and have been explored for use in the fluorescent probe, 29,36,37 cancer treatment, 38 polyamine detection, 39 and dye-sensitized solar cells. 40,41 It has been reported that PPCy dyes, with appropriate structural design, can show the properties of J-aggregates in the aggregated state. [29][30][31]42 Nevertheless, the reason why PPCy forms Jaggregates remains unclear.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the fabrication of the solar cells, we used 9μm-thick transparent electrodes and different electrolytes containing different redox mediators with different transparency in the visible range with the aim of improving the CRI of the cells. Three electrolytes were tested, the first two ones being home-made electrolytes based on iodine and cobalt-based redox couples 75,76 and the last one being an acetonitrile sulfurothiolate/iodide hybrid electrolyte, 77 commercialized by G-Lyte. From the performances reported in Table 3, it can be seen that the cells containing the iodine or mixed sulfurothioate/iodide electrolytes show the best performances with a PCE above 2.1%, which is mainly due to current densities above 6.5 mA cm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed the propensity of PPcy dyes to aggregate on the TiO 2 surface. 20 Aggregates are well-known to limit the injection process by quenching the dye excited state. 30 To prevent aggregation a co-adsorbent such as The CDCA concentration is 50 mM for TB179, and for TB202, concentrations are 0, 10 and 30 mM (dashed, short-dashed and dotted).…”
Section: Synthesismentioning
confidence: 99%